162k views
2 votes
Can please someone help me with this calculus problem? Thanks! ∫(4x-6)(x²-3x+1)^5 dx

User Lemiant
by
5.5k points

1 Answer

6 votes

Looks like the integral is


I=\displaystyle\int (4x-6)(x^2-3x+1)^5\,\mathrm dx

If you we substitute
y=x^2-3x+1 and
\mathrm dy=(2x-3)\,\mathrm dx, we get


I=\displaystyle2\int(2x-3)(x^2-3x+1)^5\,\mathrm dx=2\int y^5\,\mathrm dy

Now use the power rule, and replace y accordingly:


I=\frac{2y^6}6+C=\frac{y^6}3+C=\boxed{\frac{(x^2-3x+1)^5}3+C}

User Filimonic
by
5.3k points